Analysis of rhodamine b content in beef sausages sold in yogyakarta city market using visible spectrophotometry method - Salamah, Nina; Kurniaty, Santyas (Universitas Ahmad Dahlan, 2022)
Rhodamine B is a synthetic dye commonly used as a textile dye. According to the Minister of Health of the Republic of Indonesia No. 033 of 2012, rhodamine B is an additional colorant prohibited from being used in food products because of its carcinogenicity. This study aimed to determine the presence of rhodamine B in beef sausages sold at the Yogyakarta City Market by visible spectrophotometry. The sample used in this study was a beef sausage with a reddish-pink characteristic and without a brand. The result analysis method used in determining the qualitative test is by comparing the sample wavelength with the wavelength of the Rhodamine B standard and using the Thin Layer Chromatography (TLC) method. In the quantitative analysis, the Visible Spectrophotometry method was used. The data obtained were then analyzed using the SPSS Kolmogorov-Smirnov method, then ANOVA was used. The results of the qualitative test study obtained three positive samples containing Rhodamine B from a total of 7 samples tested. Determination of Rhodamine B levels in samples using Visible Spectrophotometry with a maximum wavelength of 556.0 nm. Rhodamine B levels obtained in samples A, C, and G were 1.06 ± 0.67; 0.87 ± 0.81, and 1.04 ± 0.82 ppm. Conclusions in the Kolmogorov-Smirnov test, the data were normally distributed, and the ANOVA results showed no differences in levels between samples.